1985
DOI: 10.1007/bf00235916
|View full text |Cite
|
Sign up to set email alerts
|

Direction-selective single units in the nucleus lentiformis mesencephali of the pigeon (Columba livia)

Abstract: The receptive field properties of single units within the nucleus lentiformis mesencephali (LM) of the pigeon were studied using electrophysiological methods. Previous studies have suggested that the avian LM may be homologous to the nucleus of the optic tract (NOT) in mammals. Single units in the pigeon LM are similar to mammalian NOT units in that they are direction-selective, mostly for horizontal directions, velocity-selective, have large visual receptive fields and respond preferentially to large stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
102
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 26 publications
3
102
0
Order By: Relevance
“…The accessory optic system of birds encodes optic flow produced when an observer moves relative to their environment. Its neurons have wide receptive fields and are directionally biased (14). One of the key accessory optic system nuclei is the lentiformis mesencephali, and it is hypertrophied in all birds capable of hovering, including transient hovering (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accessory optic system of birds encodes optic flow produced when an observer moves relative to their environment. Its neurons have wide receptive fields and are directionally biased (14). One of the key accessory optic system nuclei is the lentiformis mesencephali, and it is hypertrophied in all birds capable of hovering, including transient hovering (15).…”
Section: Discussionmentioning
confidence: 99%
“…An example of variable sensory integration comes from restrained pigeons that exhibit different head stabilization reflexes and tail responses to visual and vestibular perturbations during simulated flight than during resting conditions (16,17). At the level of sensory neurons, cells of the avian accessory optic system are divided into populations that differ in maximum sensitivity to either fast or slow motion (14,18,19). The functional roles and the relative abundance and distribution of fast and slow cells have not been described in any bird.…”
Section: Discussionmentioning
confidence: 99%
“…In pigeons and some other birds, when walking on the ground, a 'headbobbing' reflex also stabilises the head (Dunlap and Mowrer, 1930;Friedman, 1975;Frost, 1978;Davies and Green, 1988;Green et al, 1994;Troje and Frost, 2000;Fujita, 2003). The fundamental role of the nucleus of the optic basal root (nBOR) and the pretectal nucleus lentiformis mesencephali (nLM) in the elaboration of optokinetic responses in birds is well established (Britto et al, 1981;Mc Kenna andWallman, 1981, 1985;Morgan and Frost, 1981;Gioanni et al, 1983aGioanni et al, ,b, 1984Winterson and Brauth, 1985;Telford and Frost, 1989;Frost, 1990a,b, 1999;Wylie et al, 1998a;Frost et al, 1990;Fu et al, 1998a,b;Zhang et al, 1999;Wang et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on various species have reported that motionsensitive neurons are selective for the direction and speed of visual stimulus motion in the visual cortex (Maunsell and Van Essen, 1983;Petersen et al, 1985;Hammond et al, 1988;Lisberger and Movshon, 1999;Priebe and Lisberger, 2002;Liu and Newsome, 2003) as well as in the pretectum and the accessory optic system (Winterson and Brauth, 1985;Natal and Britto, 1987;Soodak and Simpson, 1988;Hoffmann and Distler, 1989;Mustari and Fuchs, 1989;Frost et al, 1990;Klauer et al, 1990;Wolf-Oberhollenzer and Kirschfeld, 1994;Li et al, 1996;Fu et al, 1998a,b;Zhang et al, 1999;Gu et al, 2001;Ibbotson and Price, 2001;Wang et al, 2001;Clifford and Ibbotson, 2003;Crowder et al, 2003). However, motion is physically described by its acceleration, as well as its direction and speed.…”
Section: Introductionmentioning
confidence: 99%